2004
DOI: 10.1536/jhj.45.297
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Sauna Therapy Reduces Urinary 8-Epi-Prostaglandin F2.ALPHA.

Abstract: SUMMARYWe have reported that repeated sauna therapy improves impaired vascular endothelial function in a patient with coronary risk factors. We hypothesized that sauna therapy decreases urinary 8-epi-prostaglandin F 2α (PGF 2α ) levels as a marker of oxidative stress and conducted a randomized, controlled study. Twenty-eight patients with at least one coronary risk factor were divided into a sauna group (n = 14) and non-sauna group (n = 14). Sauna therapy was performed with a 60°C far infrared-ray dry sauna fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 21 publications
1
75
0
3
Order By: Relevance
“…[17][18][19][20][21]29,30 In the present study, we extend these findings to show that FIR radiation exerts a potent antiinflammatory effect on vascular endothelium. We observed that FIR radiation inhibits the TNF-␣-mediated expression of the adhesion molecules VCAM-1, ICAM-1, and E-selectin, as well as the chemoattractants MCP-1 and IL-8.…”
Section: Discussionsupporting
confidence: 74%
“…[17][18][19][20][21]29,30 In the present study, we extend these findings to show that FIR radiation exerts a potent antiinflammatory effect on vascular endothelium. We observed that FIR radiation inhibits the TNF-␣-mediated expression of the adhesion molecules VCAM-1, ICAM-1, and E-selectin, as well as the chemoattractants MCP-1 and IL-8.…”
Section: Discussionsupporting
confidence: 74%
“…24 We have reported that 2 weeks of Waon therapy decreased urinary concentrations of 8-epi-PGF2α, a marker of oxidative stress, in patients with at least one atherosclerotic risk factor. 13 However, the effect of Waon therapy on oxidative stress in CHF has not been elucidated. The purpose of the present study was to clarify the effect of Waon therapy on oxidative stress in CHF patients and address its mechanism using cardiomyopathic hamsters with heart failure.…”
Section: Effect Of Waon Therapy On Oxidative Stress In Chfmentioning
confidence: 99%
“…12 In addition, we demonstrated that 2 weeks of Waon therapy significantly decreased urinary 8-epi-PGF2α levels in patients with at least 1 atherosclerotic risk factor, when compared to those of patients who did not undergo Waon therapy. 13 Thus, Waon therapy reduces oxidative stress and improves vascular function in patients with atherosclerotic risk factors.…”
Section: Effect Of Waon Therapy On Oxidative Stress In Chfmentioning
confidence: 99%
“…Urinary 8-epi-PGF2α levels were significantly decreased in the treated patients when compared with controls. 12 Thus, Waon therapy reduces oxidative stress and improves vascular function in patients with atherosclerosis risk factors.…”
Section: Effect Of Waon Therapy On Lifestylerelated Diseasesmentioning
confidence: 99%
“…11, 12 In this review, we summarize the beneficial effects of Waon therapy on cardiovascular disease.…”
mentioning
confidence: 99%